Nitrate deficiency decreased photosynthesis and oxidation-reduction processes, but increased cellular transport, lignin biosynthesis and flavonoid metabolism revealed by RNA-Seq in Oryza sativa leaves. - Cai-Hong Shao; Cai-Fei Qiu; Yin-Fei Qian; Guang-Rong Liu (PLoS ONE)
Rice cultivar "Weiyou916" (Oryza sativa L. ssp. Indica) were cultured with control (10 mM NO3-) and nitrate deficient solution (0 mM NO3-) for four weeks. Nitrogen (N) deficiency significantly decreased the content of N and P, dry weight (DW) of the shoots and roots, but increased the ratio of root to shoot in O. sativa. N deficiency decreased the photosynthesis rate and the maximum quantum yield of primary photochemistry (Fv/Fm), however, increased the intercellular CO2 concentration and primary fluorescence (Fo). N deficiency significantly increased the production of H2O2 and membrane lipid peroxidation revealed as increased MDA content in O. sativa leaves. N deficiency significantly increased the contents of starch, sucrose, fructose, and malate, but did not change that of glucose and total soluble protein in O. sativa leaves. The accumulated carbohydrates and H2O2 might further accelerate biosynthesis of lignin in O. sativa leaves under N limitation. A total of 1635 genes showed differential expression in response to N deficiency revealed by Illumina sequencing. Gene Ontology (GO) analysis showed that 195 DEGs were found to highly enrich in nine GO terms. Most of DEGs involved in photosynthesis, biosynthesis of ethylene and gibberellins were downregulated, whereas most of DEGs involved in cellular transport, lignin biosynthesis and flavonoid metabolism were upregulated by N deficiency in O. sativa leaves. Results of real-time quantitative PCR (RT-qPCR) further verified the RNA-Seq data. For the first time, DEGs involved oxygen-evolving complex, phosphorus response and lignin biosynthesis were identified in rice leaves. Our RNA-Seq data provided a global view of transcriptomic profile of principal processes implicated in the adaptation of N deficiency in O. sativa and shed light on the candidate direction in rice breeding for green and sustainable agriculture.